Overview of Poverty and Social Exclusion in the Western Balkans - Gordana Matković (Stanovništvo)
During the last 15 years the entire Western Balkan region has undergone dramatic changes. With the fall of the Berlin wall and the disintegration of the former Yugoslavia, new states were formed and transition started, although in some countries it was quite delayed. Simultaneously, during the nineties, much of the region experienced wars and destruction, waves of refugees, internal displacement of population, devastation of the economy, demolition of institutions and impoverishment of citizens.